Upaya Advokasi Dan Peningkatan Partisipasi Dalam Melakukan Pemantauan Jentik Nyamuk Aedes Pada Siswa SMP N 12 Kota Tanjung Pinang - Rinaldi Daswito (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2019)
Tanjungpinang Timur District is the most common district of Dengue Hemorrhagic Fever (DHF) every year. During the last 5 years deaths due to DHF always occur in Tanjungpinang Timur District. Need to trigger the community to participate in the activities of one house one larvae monitor (JUMANTIK) to eradicate mosquito breeding places at home. This community service activity aimed to motivate the community to participate in monitoring mosquito breeding sites through the responsibility of JUMANTIK by forming a task force called the school larvae detective (DETIK) and also having an active role in monitoring larvae in their homes. Community service was carried out with preliminary survey stages, situation analysis, getting to know and interacting with the school, stakeholder advocacy, conducting triggering to increase student participation to perform PSN and larvae monitoring, forming committees and members of detective detective, conducting technical guidance and evaluating and strengthening commitments in making changes in behavior. A special committee had been formed in the form of